2019
DOI: 10.1101/666909
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AddingMASP1to the lectin pathway – leprosy association puzzle: hints from gene polymorphisms and protein levels

Abstract: 38 39 Background: Deposition of complement factors on Mycobacterium leprae 40 may enhance phagocytosis. Such deposition may occur through the lectin 41 pathway of complement. Three proteins of the lectin pathway are produced 42 from the gene MASP1: Mannan-binding lectin-associated serine protease 1 43 (MASP-1) and MASP-3 and mannan-binding lectin-associated protein of 44 44 kDa (MAp44). Despite their obvious importance, the roles played by these 45 proteins have never been investigated in leprosy disease. Meth… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Some clinical associations of MASP-1, MASP-3, and MAp44 other than 3MC have been reported. For example, Weinschutz Mendes et al (2020) found that polymorphisms influencing serum concentrations of MASP-3/MAp44 modulate susceptibility to leprosy [ 33 ]. Larsen et al (2019) showed that low MASP-1 concentrations were associated with clotting disorders in patients with septic shock [ 34 ].…”
Section: The Masp1/3 Gene and Its Products—maspmentioning
confidence: 99%
“…Some clinical associations of MASP-1, MASP-3, and MAp44 other than 3MC have been reported. For example, Weinschutz Mendes et al (2020) found that polymorphisms influencing serum concentrations of MASP-3/MAp44 modulate susceptibility to leprosy [ 33 ]. Larsen et al (2019) showed that low MASP-1 concentrations were associated with clotting disorders in patients with septic shock [ 34 ].…”
Section: The Masp1/3 Gene and Its Products—maspmentioning
confidence: 99%